Indirect costs constitute a major part of the total economic burden of obesity: a Finnish population-based cohort study - Aino Vesikansa; Juha Mehtälä; Susanna Aspholm; Kirsi Kallio-Grönroos; Katja Mutanen; Annamari Lundqvist; Tiina Laatikainen; Tero Saukkonen; Kirsi H. Pietiläinen (BMC Public Health)
Abstract Background The growing prevalence of overweight and obesity (OB) poses a considerable economic burden worldwide. However, nationally representative, detailed analyses estimating the total burden of OB are few. We characterized direct, indirect, and total costs of overweight and obesity in a population-based cohort of Finnish adult individuals and evaluated the additional total costs attributed to overweight and obesity. Methods The study cohort included 5,587 randomly-selected individuals (≥18 years of age) who participated in the national FinHealth 2017 health examination survey. The main study group consisted of working-age individuals (18–64 years of age; n = 3,914). Individual-level data were collected from the nationwide registers by the Finnish Institute for Health and Welfare (healthcare resource utilization), Social Insurance Institution of Finland (prescription medications, sick leaves, disability pensions, rehabilitation periods), and Statistics Finland (deaths). Indirect costs were calculated using the Human Capital Approach, and direct costs were based on the medication purchases and healthcare resource use. Results The mean annual indirect costs were €1,683 (SD, €6,395) per person for the working-age individuals with normal-weight (NW), €2,957 (€8,797) for individuals with overweight (OW), €4,488 (€11,607) for individuals with class I obesity (OBI), and €4,654 (€11,383) for individuals with class II–III obesity (OBII–III). The mean annual total (direct + indirect) costs were €3,314 (SD, €8,358) per person in the NW, €4,902 (€10,747) in the OW, €7,129 (€14,313) in the OBI, and €7,372 (€14,423) in the OBII–III groups. Compared with individuals with NW, OW was associated with 31% (rate ratio, RR, 1.31; 95% CI, 1.09–1.58; p = 0.005), OBI with 83% (RR, 1.83; 95% CI, 1.46–2.28; p < 0.001), and OBII–III with 95% (RR, 1.95; 95% CI, 1.48–2.55; p < 0.001) higher total costs in working-age individuals. When adjusted for age and sex, the predicted total annual cost difference per person was €1,124 for OW, €3,002 for OBI, and €3,443 for OBII–III compared with a person with NW. Conclusions Indirect costs constitute a major part of the total costs of obesity in the working-age population. Compared with NW, the total costs are significantly higher not only for severe obesity, but also for OW and OBI.